2004
DOI: 10.1021/cm049598q
|View full text |Cite
|
Sign up to set email alerts
|

Gate Insulators in Organic Field-Effect Transistors

Abstract: In this paper, we review recent progress in the understanding of insulator/semiconductor interfaces in organic field-effect transistors (OFETs). We would like to emphasize that the choice of gate insulator is as important for high-quality OFET devices as the semiconductor itself, especially because of the unique transport mechanisms operating in them. To date researchers have explored numerous organic and inorganic insulator materials, some of them designed to improve the morphology of the organic semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
641
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 872 publications
(673 citation statements)
references
References 68 publications
(114 reference statements)
27
641
2
3
Order By: Relevance
“…Using a polar gate insulator in OFETs is known to typically yield a relatively lower field effect mobility, than otherwise attained using for instance a dielectric insulator, for disordered OSCs [36]. When comparing our extracted mobility values to similar devices, with undoped OSCs, that are gated through a polar insulator or via an electrolyte [11,26,[36][37][38][39] we find that the values extracted for P3HT and P3HT-COOH15 seem to agree to prior reported data. The relatively much higher mobility value extracted for P3CPT leads us to suspect that there might be a different operation mechanism for P3CPT-OTFTs than for the other two polymer OSCs.…”
Section: µLin = L/(wcivds)* ∂Id/∂vgssupporting
confidence: 83%
“…Using a polar gate insulator in OFETs is known to typically yield a relatively lower field effect mobility, than otherwise attained using for instance a dielectric insulator, for disordered OSCs [36]. When comparing our extracted mobility values to similar devices, with undoped OSCs, that are gated through a polar insulator or via an electrolyte [11,26,[36][37][38][39] we find that the values extracted for P3HT and P3HT-COOH15 seem to agree to prior reported data. The relatively much higher mobility value extracted for P3CPT leads us to suspect that there might be a different operation mechanism for P3CPT-OTFTs than for the other two polymer OSCs.…”
Section: µLin = L/(wcivds)* ∂Id/∂vgssupporting
confidence: 83%
“…For example, the phenomenon might be due to a variation in the gate dielectric constant of the film with the concentration of the PMMA solution. 17 Veres et al 2,18 suggested that a higher dielectric constant induces a broadening of the density of states ͑DOS͒ at the polymer/insulator interface. This results in a decrease in the DOS at the Fermi energy and subsequently causes a lower hopping probability, leading to a suppression of the carrier mobility.…”
Section: -2mentioning
confidence: 99%
“…3 The high resistivity ͑Ͼ2 ϫ 10 15 ⍀ cm͒ and low dielectric constant ͑approximately 3, similar to that of silicon dioxide͒ of poly͑methyl methacrylate͒ ͑PMMA͒ make it potential candidate as the dielectric layer in OTFTs. 2,4 Furthermore, this polymer contains hydrophobic methyl radical groups, which can play a role as moisture inhibitors, as well as encourage good ordering of the active organic overlayer as it is deposited on the surface. 5 To date, pentacene-based OTFT devices using PMMA as the gate dielectric have shown low field-effect mobilities ͑generally less than 0.1 cm 2 V −1 s −1 ͒ due to the relatively thick film of PMMA used, low on/off current ratios ͑10 3 ͒ resulting from large leakage currents, and high threshold voltages ͑Ϫ15 to Ϫ25 V͒.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 It has also reported that PCBM molecules are intercalating between the side chains of some conjugated polymers and that this behavior influences significantly the device performance including the charge carrier transport. [21][22][23] More recently, it was also proved that PCBM molecules and/or their aggregates are miscible with P3HT and mobile in amorphous region of P3HT even at low temperature, 50 C. 24 Although charges are generally expected to be better transported in a well-ordered structure of a conjugated polymer, it has been reported that some disordered conjugated polymers [25][26][27][28][29][30] also exhibit high charge mobility in spite of their amorphous nature. Thus, it is very important to understand the charge transport mechanism in amorphous low bandgap conjugated polymer for development of high efficiency OPVs.…”
Section: Introductionmentioning
confidence: 99%